Severe head injury in the elderly: risk factor assessment and outcome analysis in a series of 100 consecutive patients at a Level 1 trauma centre - Borkar, Sachin A; Sinha, Sumit; Agrawal, Deepak; Satyarthee, Guru Dutt; Gupta, Deepak; Mahapatra, Ashok Kumar (Indian Journal of Neurotrauma, 2011)
Incidence of head injuries is rising all over the world. Very few studies have been performed regarding severe head injury in the elderly. We aimed to study the epidemiology, mode of injury, clinical profile,management, complications and outcome in severe head injury occurring in the elderly (age e"60years). One hundred consecutive patients of severe head injury(GCSd" 8) admitted at a Level 1 trauma centre from 2006 through 2008 were retrospectively analysed. The cases were reviewed in the light of epidemiology, clinico-radiological findings, associated injuries, comorbidities, surgical intervention, post-operative complications and long-term outcome. Mean age was 63.5 years± 4.64(60-85 years, 74%male). Road traffic accident was the most common mode of injury(72%). Median GCS at admission was 5(range-3-8). CT scan revealed acute subdural hematoma in 53 (53%) patients, cerebral contusion in 53, SAH in 20, extradura hematoma in 10 and diffuse axonal injury in 11 patients. Associated comorbidities included DM in 17%, CAD in 10%, hypertension in 9%, alcoholic liver disease in 8%. Associated spinal injury was observed in 10%, abdominal solid organ injury in 5, pneumothorax in 6 patients. Eighty two patients underwent operative intervention. Remaining 18 patients were managed conservatively. Forty patients(40%) developed ventilator —associated pneumonia (VAP), meningitis(16%), septicemia(20%), coagulopathy(11%) and multi-organ dysfunction syndrome (MODS)(20%). Overall mortality was 70%. Follow up was available for 24 out of the 30 survivors (80%). Median GOS score for those patients who survived was 4(3–5) at 6m follow-up period was positively correlated with pre-admission GCS score (Correlation coefficient +0.78). Mean time interval from injury to intervention, associated comorbidities, associated spinal, orthopaedic and abdominal injury; traumatic SAH on CT head all were more common in patients with ultimate unfavourable outcome as compared to patients who survived and this difference was statistically significant (p value<0.05). Severe head injury in elderly carries a high mortality owing to associated comorbidities. Pre-admission GCS score bears a positive correlation to GOS score at 6 months followup. VAP with resultant septicemia is the foremost post-operative cause of death in severe head injury in the elderly. In this regard, there is a need for an integrated multi-modality multidepartmental dedicated teamwork.
Keywords: brain injury; diffuse axonal injury; elderly; head injury; intracranial hematoma